Theory of variational stress transfer in general symmetric composite laminates containing non-uniformly spaced ply cracks. (April 2018) - Hajikazemi, M.; McCartney, L.N.; Van Paepegem, W.; Sadr, M.H.
Abstract: Ply cracking is an inherently stochastic process due to the random variability of local material properties of the plies. Such randomness in microstructure and in failure evolution generally leads to non-uniform distributions of ply cracks. Modeling this non-uniformity is a crucial factor in predicting the initiation and propagation of matrix cracks. Therefore, a novel stress-based variational model is developed to accurately predict stress transfer and stiffness reduction in general symmetric laminates containing non-uniformly spaced ply cracks. In contrast to available approaches for uniformly spaced ply cracks based on the unit cell, the analysis is carried out for the entire laminate. Results derived from the developed method for thermo-elastic properties of the cracked laminates show an excellent agreement with finite element results. Moreover, the accuracy of predictions based on an approximate approach is discussed using a comprehensive analysis of various laminates and crack patterns for both carbon and glass fibre systems.